Handbook of special librarianship and information work - Batten, William Edward; Ashworth, Wilfred (London : Aslib, 1975)
The book is a contribution of various authors that examines different topics on Librarianship, library and information services and processes. It contains vital information for both practicing librarian and students of library and information science.
First-3d eds. by Wilfred Ashworth.
Includes bibliographies and index.
usc 13/6/17
Loans
Keywords: Special libraries; Information services; Library science